RELATIONSHIP BETWEEN FRIENDSHIP QUALITY AND ANXIETY IN FACING PHYSICAL CHANGES DURING PUBERTY IN FEMALE STUDENTS OF ELEMENTARY SCHOOL - Masruroh Masruroh; Ida Rahmawati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Friends have the most influence in an individual's life. Friendship contains specific elements, such as trust, openness, sharing of ups and downs, and learning to deal with conflict. Puberty children try to have friends to share their feelings with others. Because with good friendship will reduce minimize the anxiety they experience at puberty (Wulandari, Kustriyani, & Fiyannti, 2018). Objectives: The Purpose of this study to determine the relationship between friendship quality and anxiety facing the physical changes of puberty in female students at SDIT Bakti Insani Sleman Yogyakarta. Methods: This study was a quantitative research with survey method, with a total sampling of 47 respondents. Research instruments with questionnaires, the questionnaire was adopted from Marvienda (2007), researchers used a measuring instrument in the form of a friendship quality scale and anxiety scale of female students during puberty. Data analysis using person product moment. Results: The result showed respondents age 100% at the early adolescent stage, 74.5% respondents had not yet menarche, 25.5% had menarche, the average value of friendship quality was 84.89 and the average anxiety value was 63.91. The results showed that there was no relationship between the quality of friendship with anxiety facing physical changes during puberty in female students at SDIT Bakti Insani Sleman Yogyakarta (r = -.38, p-value = .802). Conclusion: This study found that the majority of respondents were in their early teens and only a small proportion had experienced menarche. The average value of high friendship quality shows that the quality of friendship is also high and the average value of anxiety in the medium shows moderate anxiety. The implications of this study are as input or consideration in preparing adolescent reproductive health starting from the beginning of puberty at school. Keywords: Quality of Friendship, Anxiety, Puberty, Physical Changes